Report on Marriage Rights for Same-Sex Couples in New York - of the City of New York, The Association of the Bar (Columbia Journal of Gender and Law, 2004)
There is currently a national debate over the right of lesbian and gay couples to enter into state-sanctioned marriage. Much of this debate stems from Vermont’s recent legislation permitting same-sex civil unions. Lawsuits in Hawaii and Alaska attacking the constitutionality of prohibitions on same-sex marriage have also fueled the debate. In addition, many states are currently considering, and some have adopted, legislation attempting to prevent recognition of same-sex marriages performed in sister states. Most notably, in 1996, Congress enacted the Defense of Marriage Act (DOMA), which could give states that enact such legislation further ammunition in their efforts to deny recognition to same-sex marriages that may be legally sanctioned in sister states. The constitutionality of measures denying recognition of same-sex marriage is in doubt, especially in light of the United States Supreme Court’s apparent shift in its consideration of gay and lesbian rights. Fifteen years ago, the Court found that a state sodomy statute enforced only against homosexuals violated no constitutionally protected rights. In contrast, in 1996, the Court found that by subjecting one group to a disadvantage that no other group had to suffer, a state constitutional amendment that barred anti-discrimination measures protecting lesbians and gay men violated the United States Constitution’s Equal Protection Clause. In so doing, the Court took the remarkable step of invoking the landmark dissent in Plessy v. Ferguson in the opening paragraph of its decision: “[T]he Constitution ‘neither knows nor tolerates classes among its citizens. Unheeded then, those words now are understood to state a commitment to the law’s neutrality where the rights of persons are at stake.” The Court made clear that it would not countenance a legal distinction that raised the “inevitable inference that the disadvantage imposed is born of animosity toward the class of persons affected.”